2012
DOI: 10.1111/j.1364-3703.2012.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

A viralRNAsilencing suppressor interferes with abscisic acid‐mediated signalling and induces drought tolerance inArabidopsis thaliana

Abstract: Cucumber mosaic virus (CMV) encodes the 2b protein, which plays a role in local and systemic virus movement, symptom induction and suppression of RNA silencing. It also disrupts signalling regulated by salicylic acid and jasmonic acid. CMV induced an increase in tolerance to drought in Arabidopsis thaliana. This was caused by the 2b protein, as transgenic plants expressing this viral factor showed increased drought tolerance, but plants infected with CMVΔ2b, a viral mutant lacking the 2b gene, did not. The sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 71 publications
4
100
4
Order By: Relevance
“…However, plants in which viruses inhibit aphid resistance (or at least induce no deleterious effects on the aphids) will foster aphid survival and reproduction (Type 2 hosts: Figure 11). Although onward transmission of the virus from Type 2 hosts will be less frequent, and probably driven by overcrowding of the aphids as their populations grow, these plants may provide a safe haven for aphids during stressful periods of cold or drought [48,49] and allow the vector population to recover after a period of active transmission between Type 1 plants. When conditions improve Type 2 hosts could act as centers from which the aphids and the virus will spread to Type 1 plants and resume a more active phase of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, plants in which viruses inhibit aphid resistance (or at least induce no deleterious effects on the aphids) will foster aphid survival and reproduction (Type 2 hosts: Figure 11). Although onward transmission of the virus from Type 2 hosts will be less frequent, and probably driven by overcrowding of the aphids as their populations grow, these plants may provide a safe haven for aphids during stressful periods of cold or drought [48,49] and allow the vector population to recover after a period of active transmission between Type 1 plants. When conditions improve Type 2 hosts could act as centers from which the aphids and the virus will spread to Type 1 plants and resume a more active phase of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…; Westwood et al . ) and drastic changes in nutrient levels that both encourage dispersal of viruliferous vectors after probing and deter non‐vector herbivore feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In one way this was a surprising result because in a number of studies it has been shown that small RNA pathways affect drought responses. For example, where RNA silencing pathways have been compromised through mutation of AGO1 or DCLs 1–4, the mutant plants showed increased resistance to water loss [56], [57], [58]. Hence, although RDR1 is a component of the silencing pathway it does not appear to play a critical role in drought resistance, unlike the DCLs and AGO1.…”
Section: Discussionmentioning
confidence: 99%
“…The plant hormone treatments were SA (1 mM), methyl-JA (250 µM), ABA (50 µM) and ACC (the precursor of ethylene; 1 mM) dissolved in water. Hormone concentrations were selected on the basis of previous optimization for SA and methyl-JA [46], ACC [59], and ABA [58], [60]. Control treatment used water only.…”
Section: Methodsmentioning
confidence: 99%